2020
DOI: 10.1155/2020/3591274
|View full text |Cite
|
Sign up to set email alerts
|

Successful A2 to B Deceased Donor Kidney Transplant after Desensitization for High-Strength Non-HLA Antibody Made Possible by Utilizing a Hepatitis C Positive Donor

Abstract: Desensitization using plasma exchange can remove harmful antibodies prior to transplantation and mitigate risks for hyperacute and severe early acute antibody-mediated rejection. Traditionally, the use of plasma exchange requires a living donor so that the timing of treatments relative to transplant can be planned. Non-HLA antibody is increasingly recognized as capable of causing antibody-mediated renal allograft rejection and has been associated with decreased graft longevity. Our patient had highstrength non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Antibody levels decreased and an endothelial crossmatch became negative after 9 PP sessions and treatment with low-dose IVIG (100 mg/kg), 5–8 mg/ml tacrolimus, and mycophenolate mofetil (MMF) (2000 mg daily). Other case reports 82-84 also showed that PP was successful in treating AMR in renal transplant patients with anti-AT1R antibodies but without DSAs. Although AT1R antibody titers sometimes returned to the maximal detection level after treatment, refractory AMR was not observed.…”
Section: Therapeutic Approachesmentioning
confidence: 87%
“…Antibody levels decreased and an endothelial crossmatch became negative after 9 PP sessions and treatment with low-dose IVIG (100 mg/kg), 5–8 mg/ml tacrolimus, and mycophenolate mofetil (MMF) (2000 mg daily). Other case reports 82-84 also showed that PP was successful in treating AMR in renal transplant patients with anti-AT1R antibodies but without DSAs. Although AT1R antibody titers sometimes returned to the maximal detection level after treatment, refractory AMR was not observed.…”
Section: Therapeutic Approachesmentioning
confidence: 87%